Effects of polycyclic aromatic hydrocarbons (PAHs) on pregnancy, placenta, and placental trophoblasts - Yifeng Dai; Xijin Xu; Xia Huo; Marijke M. Faas (Ecotoxicology and Environmental Safety, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are a group of persistent organic pollutants that are carcinogenic, mutagenic, endocrine-toxic, and immunotoxic. PAHs can be found in maternal and fetal blood and in the placenta during pregnancy. They may thus affect placental and fetal development. Therefore, the exposure levels and toxic effects of PAHs in the placenta deserve further study and discussion. This review aims to summarize current knowledge on the effects of PAHs and their metabolites on pregnancy and birth outcomes and on placental trophoblast cells. A growing number of epidemiological studies detected PAH-DNA adducts as well as the 16 high-priority PAHs in the human placenta and showed that placental PAH exposure is associated with adverse fetal outcomes. Trophoblasts are important cells in the placenta and are involved in placental development and function. In vitro studies have shown that exposure to either PAH mixtures, benzo(a)pyrene (BaP) or BaP metabolite benzo(a)pyrene-7,8-dihydrodiol-9,10-epoxide (BPDE) affected trophoblast cell viability, differentiation, migration, and invasion through various signaling pathways. Furthermore, similar effects of BPDE on trophoblast cells could also be observed in BaP-treated mouse models and were related to miscarriage. Although the current data show that PAHs may affect placental trophoblast cells and pregnancy outcomes, further studies (population studies, in vitro studies, and animal studies) are necessary to show the specific effects of different PAHs on placental trophoblasts and pregnancy outcomes.